MSC-sEV treatment polarizes pro-fibrotic M2 macrophages without exacerbating liver fibrosis in NASH - Zhang, Bin (2023)
Mesenchymal stem/stromal cell small extracellular vesicles (MSC-sEVs) have shown promise in treating a wide range of animal models of various human diseases, which has led to their consideration for clinical translation. However, the possibility of contraindication for MSC-sEV use is an important consideration. One concern is that MSC-sEVs have been shown to induce M2 macrophage polarization, which is known to be pro-fibrotic, potentially indicating contraindication in fibrotic diseases such as liver fibrosis. Despite this concern, previous studies have shown that MSC-sEVs alleviate high-fat diet (HFD)-induced non-alcoholic steatohepatitis (NASH). To assess whether the pro-fibrotic M2 macrophage polarization induced by MSC-sEVs could worsen liver fibrosis, we first verified that our MSC-sEV preparations could promote M2 polarization in vitro prior to their administration in a mouse model of NASH. Our results showed that treatment with MSC-sEVs reduced or had comparable NAFLD Activity Scores and liver fibrosis compared to vehicle- and Telmisartan-treated animals, respectively. Although CD163+ M2 macrophages were increased in the liver, and serum IL-6 levels were reduced in MSC-sEV treated animals, our data suggests that MSC-sEV treatment was efficacious in reducing liver fibrosis in a mouse model of NASH despite an increase in pro-fibrotic M2 macrophage polarization.